2018
DOI: 10.1039/c7re00206h
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and advanced kinetic models for characterization of chain-growth copolymerization: the state-of-the-art

Abstract: A detailed overview is given on the currently developed analytical and advanced kinetic models to calculate the main bulk/solution chain-growth copolymerization characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 136 publications
0
42
0
Order By: Relevance
“…4b, c. Figure 4a shows that for both the 10 and 50 mol % initial functionality loading the well-known terminal Mayo-Lewis 41,42 behavior is followed:
Fig. 4Conventional analysis of 2-oxazoline comonomer incorporation.
…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…4b, c. Figure 4a shows that for both the 10 and 50 mol % initial functionality loading the well-known terminal Mayo-Lewis 41,42 behavior is followed:
Fig. 4Conventional analysis of 2-oxazoline comonomer incorporation.
…”
Section: Resultsmentioning
confidence: 95%
“…Conventional analysis of the comonomer incorporation in a copolymerization process focuses in addition mostly on the instantaneous average copolymer composition F A,inst 42 , which reflects the average amount of comonomer A incorporated in all active chains at a certain moment for a given molar fraction of A in the reaction mixture ( f A ).…”
Section: Resultsmentioning
confidence: 99%
“…As in many theoretical derivations, in several fields one can opt to describe a certain phenomenon in a differential or integral manner. [152,153] In the present section, we put forward the most important continuum-based integral constitutive models. To predict the viscoelastic deformation behavior at the nonlinear strain region, the single integral K-BKZ constitutive model, as first proposed 50 years ago, [154][155][156] is often used.…”
Section: Continuum-based Integral Constitutive Modelsmentioning
confidence: 99%
“…In practice, it is advisable to identify the most dominant reaction steps, taking into account that more recent research has indicated the relevance of penultimate monomer unit (PMU) effects as well [66]. This implies that, to describe the reactivity of a macroradical, one should potentially also consider the monomer unit preceding the unit containing the radical center (the so-called penultimate monomer unit), instead of a conventional approach focusing only on the terminal monomer unit: hence, the unit with the radical center [67][68][69].…”
Section: Radical Reaction Mechanisms For Thermal Pmma Chemical Recyclingmentioning
confidence: 99%